Effects Cognitive Stimulation Therapy For Dementia: Systematic Review - Elmiyanti, Ni Ketut; Salamung, Niswa (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction:  The prevalence of dementia in the elderly continues to increase and the need for appropriate interventions, one therapy that can be used is cognitive stimulation therapy (CST). The aim of this study was to analyze the level of evidence on the effectiveness of cognitive simulation therapy for elderly people with dementia.Methods: The systematic review of this study pays attention to the inclusion criteria, namely articles in English, using cognitive stimulation therapy interventions in the study and the population is the elderly. Articles sourced from the electronic databases Scopus, PubMed, Science Direct, Scholar, and ProQuest, were identified as appropriate and relevant to this topic. Fifteen research studies were selected and analyzed because they qualify as review articles for systematic review.Results: Thirteen studies were Randomized Control Trial (RCT), one controlled clinical trial and one group pretest-posttest. The results showed that CST was very influential on memory, language comprehension, and orientation for cognitive improvement in mild to moderate dementia. CST should be done periodically to get good results. In addition, the effect of CST may differ according to what factors are emphasized in the program.Conclusion: CST in the elderly with mild to moderate dementia can significantly improve overall cognitive function.